Coagulation Dysfunction in Acute Respiratory Distress Syndrome and Its Potential Impact in Inflammatory Subphenotypes - Livingstone, Samantha A.; Wildi, Karin S.; Dalton, Heidi J.; Usman, Asad; Ki, Katrina K.; Passmore, Margaret R.; Li Bassi, Gianluigi; Suen, Jacky Y.; Fraser, John F. (Frontiers in Medicine, 2021)
The Acute Respiratory Distress Syndrome (ARDS) has caused innumerable deaths worldwide since its initial description over five decades ago. Population-based estimates of ARDS vary from 10-86 cases per 100,000, with the highest rates reported in Australia and the United States (1). This syndrome is characterised by a breakdown of the pulmonary alveolo-epithelial barrier with subsequent severe hypoxaemia and disturbances in pulmonary mechanics. The underlying pathophysiology of this syndrome is a severe inflammatory reaction and associated local and systemic coagulation dysfunction that leads to pulmonary and systemic damage, ultimately causing death in up to 40% of patients. Since inflammation and coagulation are inextricably linked throughout evolution, it is biological folly to assess the two systems in isolation when investigating the underlying molecular mechanisms of coagulation dysfunction in ARDS. Although the body possesses potent endogenous systems to regulate coagulation, these become dysregulated and no longer optimally functional during the acute phase as ARDS, further perpetuating coagulation, inflammation and cell damage. The inflammatory ARDS subphenotypes address inflammatory differences but neglect the equally important coagulation pathway. A holistic understanding of this syndrome and its subphenotypes will improve our understanding of underlying mechanisms that then drive translation into diagnostic testing, treatments and improve patient outcomes.